Deregulated Production of Protective Cytokines in Response to Candida albicans Infection in Patients with Chronic Mucocutaneous Candidiasis - Lilic, Desa (American Society for Microbiology, 2003)

(untitled)
Patients with chronic mucocutaneous candidiasis (CMC) are selectively unable to clear the yeast Candida, which results in persistent debilitating infections affecting the skin, nails, and mucous membranes. The underlying defect is unknown. Recent animal studies highlighted the importance of type 1 cytokines in protection against Candida, and previous work suggested that CMC patients may exhibit altered cytokine production in response to Candida. Based on these findings, in this study we investigated cytokine production in CMC patients by assessing a range of inflammatory, anti-inflammatory, type 1, and type 2 cytokines (interleukin-2 [IL-2], IL-4, IL-5, IL-6, IL-10, IL-12, gamma interferon [IFN-γ], tumor necrosis factor alpha [TNF-α]) in whole-blood cultures in response to five different fractions of Candida albicans (carbohydrate, purified mannan, and protein-rich fractions, etc.), as well as non-Candida antigens. Our results demonstrate that cytokine production is deregulated in a Candida-specific way for some cytokines (IL-2, IL-10), is deregulated more generally for other cytokines (IL-12, IL-6, IFN-γ), and is not markedly altered for still other cytokines (TNF-α, IL-4, IL-5). The most notable finding in CMC patients was the markedly impaired production of IL-12 in parallel with dramatically increased levels of IL-6 and IL-10 that occurred selectively in response to Candida. These results suggest that patients with CMC have impaired production of type 1-inducing cytokines (possibly a macrophage or dendritic cell defect?), which could result in an inability to mount protective cell-mediated responses and a failure to clear Candida. Continued tissue damage and inflammation may trigger production of high levels of inhibitory cytokines, such as the IL-10 production seen in our study, which would further reduce production of type 1-inducing cytokines in a positive feedback loop leading to persistent infection.